Phylogenetic and Spatiotemporal Analyses of the Complete Genome Sequences of Avian Coronavirus Infectious Bronchitis Virus in China During 1985–2020: Revealing Coexistence of Multiple Transmission Chains and the Origin of LX4-Type Virus - Fan, Wensheng; Chen, Jiming; Zhang, Yu; Deng, Qiaomu; Wei, Lanping; Zhao, Changrun; Lv, Di; Lin, Liting; Zhang, Bingsha; Wei, Tianchao; Huang, Teng; Wei, Ping; et al. (Frontiers in Microbiology, 2022)
Infectious bronchitis virus (IBV) causes considerable economic losses to poultry production. The data on transmission dynamics of IBV in China are limited. The complete genome sequences of 212 IBV isolates in China during 1985-2020 were analyzed the characteristics of phylogenetic tree, recombination events, dN/dS ratios, temporal dynamics and phylogeographic relationships. The LX4-type (GI-19) was found to have the highest dN/dS ratios and has been the most dominant genotype since 1999, and the Taiwan-I-type (GI-7) and New-type (GVI-1) showed an increasing trend. Total 59 recombinants were identified and multiple recombination events between the field and vaccine strains were found in 24 isolates, and the 4/91-type (GI-13) isolates were found to be more prone to involving in the recombination. Bayesian phylogeographic analyses indicated that the Chinese IBVs were originated in Liaoning province in the early 1900s. The LX4-type viruses were traced back to Liaoning province in the late 1950s and had multiple transmission routes in China and two major transmission routes in the world. Viral phylogeography identified three spread regions for IBVs (including LX4-type) in China: The northeastern China (Heilongjiang, Liaoning and Jilin), the north and central China (Beijing, Hebei, Shanxi, Shandong and Jiangsu) and the Southern China (Guangxi and Guangdong). Shandong has been the epidemiological center of IBVs (including LX4-type) in China. Overall, our study highlighted the reasons why the LX4-type viruses had become the dominant genotype and its origin and transmission routes, providing more targeted strategies for the prevention and control of IB in China.